The Italian version of the Pediatric Quality of Life Inventory™ (PEDSQL™) 3.0 healthcare satisfaction hematology/oncology module: reliability and validity in radiation oncology - Elisa Marconi; Francesco Beghella Bartoli; Elisa Meldolesi; Silvia Mariani; Giulia Panza; Alessia Nardangeli; Loredana Dinapoli; Teresa Carmen Lees; Antonella Guido; Angela Mastronuzzi; Antonio Ruggiero; Maria Antonietta Gambacorta; et al. (Health and Quality of Life Outcomes, 2023)
Abstract Background Health-related quality of life (HRQOL) measurement has become an important health care outcome even in oncological pediatric scenario. During radiation therapy care path, pediatric patients and their relatives may suffer from emotional and psychosocial distress not only related to cancer diagnosis, but also due to the procedure and the required daily routine. Despite the high prevalence of psychosocial consequences in this setting, instruments that inquire pediatric HRQOL and healthcare satisfaction have rarely been studied in Italy. Purpose of this study was to investigate reliability and linguistic validation of the PedsQL™ healthcare satisfaction Hematology/Oncology module from its original English version to Italian language. Methods Three phases standard procedure of cross-culture adaptation were used to create Italian version of PedsQL™ healthcare satisfaction Hematology/Oncology module. Forward translations and backward translations were performed. Finally, a pilot-testing for understandability of the ‘pre-final’ version was conducted with parents of children attending our Radiotherapy Center using two methodologies of Cognitive Interviewing (“Think-aloud Interviews” and “Respondent Debriefing”), in order to obtain the final Italian version of the PedsQL™ healthcare satisfaction Hematology/Oncology module. Results Twenty-five parents (2 father, 23 mothers) were recruited during their children’s radiotherapy treatment and the grammatically and conceptually acceptable pre-final version of the PedsQL™ Healthcare Satisfaction Hematology/Oncology Module was administered. The questionnaire was well understood reflecting its linguistic adaptation. Compliance with questionnaire administration was optimal. All subjects stated that the questions were interesting to express their opinion, most of them reported that all the questions of each section were clearly comprehensible and easy to understand, suggesting minimal changes that were double-checked with back translation. Furthermore, six of them spontaneously asked to complete the questionnaire in order to review the assistance received during radiotherapy. Conclusion Our Italian version of the PedsQL™ 3.0 Healthcare Satisfaction Hematology/Oncology Module seems to be a valid and functional instrument to indagate Healthcare Satisfaction.